Anaerobic capacity of amateur mountain bikers during the first half of the competition season - Zarzeczny, R. J.; Podlesny, M.; Polak, A. (Biology of Sport, 2013)
Sustained aerobic exercise not only affects the rate of force development but also decreases peak power development. The aim of this study was to investigate whether anaerobic power of amateur mountain bikers changes during the first half of the competition season. Eight trained cyclists (mean ± SE: age: 22.0 ±0.5 years; height: 174.6 ± 0.9 cm; weight: 70.7 ± 2.6 kg) were subjected to an ergocycle incremental exercise test and to the Wingate test on two occasions: before, and in the middle of the season. After the incremental exercise test the excess post-exercise oxygen consumption was measured during 5-min recovery. Blood lactate concentration was measured in the 4th min after the Wingate test. Maximum oxygen uptake increased from 60.0 ± 1.5 ml · min-1 · kg-1 at the beginning of the season to 65.2 ± 1.4 ml · min-1 · kg-1 (P<0.05) in the season. Neither of the mechanical variables of the Wingate test nor excess post-exercise oxygen consumption values were significantly different in these two measurements. However, blood lactate concentration was significantly higher (P<0.001) in season (11.0 ± 0.5 mM) than before the season (8.6 ± 0.4 mM). It is concluded that: 1) despite the increase of cyclists` maximum oxygen uptake during the competition season their anaerobic power did not change; 2) blood lactate concentration measured at the 4th min after the Wingate test does not properly reflect training-induced changes in energy metabolism.